The Errors Analysis of Students’ Grammatical Writing on Narrative Text - Jamaliah Jamaliah; Ramlan Ramlan; Fauziah Fauziah; Irma Suryani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this research was to know both the type of error and the most dominant error made by students in writing narrative text at the second grade students of SMK N 1 Sigli. This study is qualitative research as suggested by Noor (2011). The purpose of this research is to analyze the errors which actually committed by students on their writing. This research is a case study which clarifies the natural circumstance. The writer collect the data by using a set of written test. The procedures of Error Analysis (EA) adopted from Corder (1974) as cited in Ellis (2008:48). The data nanalized by using table of freqency the result showed that the error made by the students can be categorized into four types of errors. Those were errors of omission, errors of addition, errors of misformation, and errors of misordering. Another result showed that the most dominant error in writing narrative text made by the students was error of misformation. In describing the type of error, it can be inferred that there are 25 items of error, which occur in the students’ sentences.